2013
DOI: 10.1016/j.cell.2013.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Immuno- and Constitutive Proteasomes Do Not Differ in Their Abilities to Degrade Ubiquitinated Proteins

Abstract: SummaryImmunoproteasomes are alternative forms of proteasomes that have an enhanced ability to generate antigenic peptides. Recently, Seifert and colleagues reported surprising observations concerning the functions of immunoproteasomes and cellular responses to interferon-γ: (1) that immunoproteasomes degrade ubiquitinated proteins faster than the constitutive proteasomes, (2) that polyubiquitin conjugates accumulate after interferon-γ treatment but then are preferentially degraded by immunoproteasomes, and (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 38 publications
9
85
2
Order By: Relevance
“…Furthermore, it has been proposed that the immunoproteasome has a higher capacity to clear ubiquitylated proteins accumulating after stimulation with IFN-␥ (Seifert et al, 2010). However, this finding too could not be reproduced by others (Nathan et al, 2013;Kincaid et al, 2012). Unlike in the previous studies, we used two different types of primary cells directly derived from knockout mice.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, it has been proposed that the immunoproteasome has a higher capacity to clear ubiquitylated proteins accumulating after stimulation with IFN-␥ (Seifert et al, 2010). However, this finding too could not be reproduced by others (Nathan et al, 2013;Kincaid et al, 2012). Unlike in the previous studies, we used two different types of primary cells directly derived from knockout mice.…”
Section: Discussionmentioning
confidence: 55%
“…Together, these findings led this group to conclude that immunoproteasomes are more efficient at maintaining protein homeostasis than are standard proteasomes 27 . In another study, no significant differences were reported in terms of the degradation of ubiquitinated proteins by immunoproteasomes and standard proteasomes under identical experimental conditions 28 . These reports clearly suggest that substantial efforts are still needed to provide confirmatory evidence regarding the role of immunoproteasomes in the maintenance of protein homeostasis.…”
Section: Immunoproteasomes: Structure Assembly Regulation and Functionmentioning
confidence: 97%
“…A role in the clearance of oxidatively damaged proteins was proposed [58, 59], especially during inflammation [59], in the regulation of tumor development, in lipid metabolism [60] and in NFκB signaling [58]. Whether immunoproteasomes have the capacity to alter the clearance of ubiquitinated proteins after interferon-Ɣ treatment, as has been proposed earlier [59] but is currently debated [61]. …”
Section: Major Alternate Forms Of the Proteasomementioning
confidence: 99%